Governance without government or: The Euro Crisis and what went wrong with European Economic Governance? - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2012)
The Great Recession after 2008 did not turn out to be as deep and severe as the Great Depression of the 1930s. According to the European Commission, this positive result is due to the fact that economic policy-makers around the world learnt their lessons from the Great Depression in stabilizing their financial systems and, moreover, that particularly the European Union and its economic governance system has become a shelter against negative external shocks in coordinating stabilization policies to maintain aggregate demand. This paper argues that the claim of the European Commission needs some qualifications: on the one hand, the lessons have not been applied appropriately in all EU and, particularly, Eurozone Member States. This is, on the other hand, not merely the result of mismanagement of individual governments but the systematic outcome of an ineffective and even counterproductive European economic governance system. Although, in the wake of the Euro Crisis some crisis control and emergency measures have been established, crisis resolution has failed as the core of the inefficient governance system - the European Stability and Growth Pact (ESGP) - has not been reformed adequately.
Keywords: B59; F15; H30; N10; 330; Euro Crisis; European Governance; Economic Policy; Finanzmarktkrise; Staatsbankrott; Europäischer Stabilitätsmechanismus; Governance-Ansatz; Internationale wirtschaftspolitische Koordination; Eurozone